A comprehensive study of the thermal response of a long-span cable-stayed bridge: From monitoring phenomena to underlying mechanisms. (1st June 2019) - Zhou, Yi; Sun, Limin
Highlights: Temperature changes in a cable-stayed bridge can be decomposed into five variables. Two modes of temperature dependencies of structural responses are discovered. Root causes of five thermal responses of cable-stayed bridges are presented. Abstract: Structural deformation and variation in internal force are important considerations with regard to bridge health monitoring. Field measurements demonstrate that thermal effects of cable-stayed bridges—which represent high-order statically indeterminate structures—are extremely complex and nearly impossible to explicate in terms of temperature-limit states assumed during the design stage. Based on monitoring data recorded for the Shanghai Yangtze River Bridge—a steel box girder, twin-tower cable-stayed bridge with a 730 m central span—simultaneous investigations were performed concerning effects of seasonal as well as diurnal temperature variations on thermally induced changes in the mid-span vertical displacement ( D T ) and horizontal projection length ( L T ) of the girder, distance between the two tower tops ( S T ), structural total or elastic strains ( ε M / ε E ) at the mid-span section and average cable tensions of the longest centre-span cables ( F T ). In terms of variation amplitudes, correlations between temperature and structural response of a cable-stayed bridge can be classified into two modes. In the first mode, annual variation amplitudes are observed to be significantly larger compared with diurnal amplitudes. This applies to parameters L T, S T and ε M . In the second mode, annual variation amplitudes approximately equal diurnal amplitudes. This is true for parameters D T, ε E and F T . Temperature variables upon which structural response of cable-stayed bridges primarily depends usually differ from one another in that L T, S T and ε M are governed exclusively by the average girder temperature while D T and F T are simultaneously determined by the cable and average girder temperatures; parameter ε E is dominated by the temperature difference between the top and bottom plates of the girder. This study establishes a sound understanding of behavioural patterns in cable-stayed bridges to facilitate the determination of feasible measurement-point locations, useful with regards to bridge-monitoring systems, as well as selection of appropriate temperature variables for thermal-response modelling.